KARAKTERISTIK PENDIDIKAN PESANTREN; SEBUAH POTRET - Ramli, Muhamad (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2018)
Islamic boarding schools have always been considered as a barrier to progress because they are considered educational institutions or religious social institutions that do not respond to change. Even so, there is no doubt that from the womb of the pesantren there have been many figures who have contributed to this country. Pesantren as a legacy of the past Indonesian Muslims grew up in the community to serve their various needs. He can serve the needs of education when people need it, especially when modern educational institutions that are generally formal, have not been able to penetrate into rural areas. At that time, even now, the pesantren world has become a symbol that connects the rural world with the outside world. Keywords: Characteristics, Pesantren, Education, Existence.